Histoid leprosy in a 12-year-old child: A rare presentation - Sandeep Anilrao Kulkarni; Namrata Chhabra; Neel Prabha (Wolters Kluwer Medknow Publications, 2016)
Histoid leprosy is a clinical variant of nodular form of lepromatous leprosy. De novo histoid leprosy in children is a rare clinical presentation. We hereby report a case of a 12-year-old child presenting with lesions of histoid leprosy.